Occupational health and safety advisory services (OHSAS) 18001 Management system adoption: assessing the determinants - Tan, Cheng Ling; Fathyah Hashim; Chu, Wee Liang (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study employed structural equation modeling (SEM) and partial least square (PLS) tools to examine the determinants (namely management commitment, work involvement, incentive and recognition, and supportive environment) involved in the adoption of OHSAS 18001 management system by industries in Malaysia. Survey data was drawn from a sample of 128 OHSAS 18001 certifi ed companies from various industries. Statistical results confi rmed that only management commitment and supportive environment positively infl uence OHSAS 18001 management system adoption, while work involvement, and incentive and recognition are not signifi cantly infl uencing OHSAS 18001 adoption. The fi ndings are useful for practitioners that are considering the adoption of OHSAS 18001 management system in their companies. This paper concludes with discussion, implications, limitations and suggestion for future study.